Overcoming Energy Storage‐Loss Trade‐Offs in Polymer Dielectrics Through the Synergistic Tuning of Electronic Effects in π‐Conjugated Polystyrenes - Yipin Cheng; Honghong Gong; Meirong Zhang; Qinglong Ji; Guanxiang Zhang; Xiao Zhang; Zhicheng Zhang (Advanced Science)
Abstract Achieving high‐performance dielectric materials remains a significant challenge due to the inherent trade‐offs between high energy storage density and low energy loss. A central difficulty lies in identifying a suitable dipolar unit that can enhance the polarity and dielectric constant of the material while effectively suppressing the high energy losses associated with polarization relaxation, charge injection, and conduction. To address this, a novel strategy is proposed that introduces electron‐donating and electron‐withdrawing substituents on the benzene ring of polystyrene‐based polymers, creating bulky dipole groups that are resistant to reorientation under an electric field. This approach mitigates relaxation losses associated with dipole reorientation and manipulates the band structure via substituent modification to suppress conduction losses. Additionally, the deformation of the π‐electron cloud under an electric field enhances the dielectric constant and energy storage density. Ultimately, the optimized chlorostyrene‐methyl methacrylate (MMA) copolymer exhibits an 85% discharge efficiency and an energy storage density of 18.3 J cm−3, nearly three times that of styrene‐based copolymers under the same conditions. This study introduces a new approach for designing high‐energy density, low‐loss polymer dielectric materials by precisely controlling electron‐donating and electron‐withdrawing effects to modulate the distribution of π‐conjugated electron clouds.